ESTETIKA FOTO PREWEDDING KARYA HENDRA LESMANA - Abdee Rangga Bhaskara Prakosa; Amoga Lelo Octaviano (Retina Jurnal Fotografi, 2023)
Hendra Lesmana is a commercial photographer who usually accepts pre-wedding photo shoot projects. Pre-wedding photos used to record moments of happiness welcoming a new life that will soon be lived by the second bride and groom. Marriage is a moment in life that is expected to create happiness and can achieve common goals later. In a pre-wedding photo shoot, many aspects need to be prepared, such as the location of the photo shoot, timing, concept determination, and approach with the client or object to be used. The object of research discussed is the work of pre-wedding photos that will be done in 2021 by Hendra Lesmana. Aesthetic theory of photography used in ideational and technical. Hendra Lesmana always takes photos in three different perspectives, namely, wide angle, medium, and close up. In nature photos he also always uses the sun as the main lighting in producing a photo. A good aesthetic role is needed in creating quality photo works. Keywords: Photography Aesthetics, Prewedding, Hendra Lesmana